1997
DOI: 10.1037/0882-7974.12.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Perceived problems for self and others: Self-protection by social downgrading throughout adulthood.

Abstract: In this study the authors investigated social downgrading as reflected in the difference between perceptions about the self and about "most people my age." A large cross-national probability sample of adults at different age levels throughout adulthood provided ratings of perceived problems expected for the self and for "most other people my age" with regard to 12 domains of life (e.g., health, marriage, and job). Results showed that with regard to all domains, younger, middle-aged, and older adults believed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 26 publications
8
76
1
1
Order By: Relevance
“…Heckhausen and Krueger interpret this finding as reflecting self-enhancement, which they argue to become more important in old age when negative expectations threaten selfesteem and perceived control. Similarly, Heckhausen and Brim (1997) suggest that the positive discrepancy between evaluations of one's own compared to most others' development serves as a means for self-protection in older adults.…”
Section: Subjective Developmental Conceptions Across Adulthoodmentioning
confidence: 99%
“…Heckhausen and Krueger interpret this finding as reflecting self-enhancement, which they argue to become more important in old age when negative expectations threaten selfesteem and perceived control. Similarly, Heckhausen and Brim (1997) suggest that the positive discrepancy between evaluations of one's own compared to most others' development serves as a means for self-protection in older adults.…”
Section: Subjective Developmental Conceptions Across Adulthoodmentioning
confidence: 99%
“…At the same time, however, older adults still described developmental trajectories for themselves that reflected typically documented beliefs of declines in desirable traits and increases in undesirable traits in later life. In a related study, Heckhausen and Brim (1997) found that older adults perceived themselves to have fewer problems relative to peers, but age differences in self-reported problems were consistent with expectations (e.g., more health problems with increasing age).…”
Section: Self-related Attitudesmentioning
confidence: 50%
“…Research has suggested that the degree to which one holds negative views of aging is in part related to concerns about one's own aging (e.g., Braithwaite, Lynd-Stevenson, & Pigram, 1993). Relatedly, older adults often have more positive attitudes about themselves than about same-aged peers (e.g., Heckhausen & Brim, 1997;Heckhausen & Krueger, 1997;Luszcz & Fitzgerald, 1986), although this is not always observed (e.g., Ryan & Kwong See, 1993). Hummert (1999) has further argued that cues associated with older adults' physical appearance and behavior may activate aging stereotypes in others, which in turn influence their behavior toward these same individuals.…”
Section: E Activators and Moderators Of Attitudesmentioning
confidence: 99%
“…Utvrđeno je da ljudi koje žale zbog neuspjeha na području vrlo relevantnom za njihovo samopoimanje osjećaju veće žaljenje kad se uspoređuju sa sebi bliskima nego sa socijalno udaljenim osobama (Tesser, 1988.;Tesser i sur., 1988.). Kad su oni s kojima se uspoređujemo slični nama (lateralne usporedbe) ili slabiji od nas na relevantnom području (silazne usporedbe), uspoređivanje može umanjiti neugodne emocije vezane uz iskustvo neuspjeha (Heckhausen i Brim, 1997.). Usporedbe s boljima od sebe povećavaju neugodne emocije povezane s neuspjehom (Aspinwall i Taylor, 1993.…”
Section: Socijalni I Razvojni Aspekti žAljenjaunclassified